Intracellular antibodies and challenges facing their use as therapeutic agents. - Lobato, M; Rabbitts, T (2003)
A key feature of antibodies is their ability to bind antigens with high specificity and affinity. This has led to the concept of intracellular antibodies (intrabodies), designed to mimic antibody-antigen binding, but inside cells. Antibody fragments comprising the antigen-binding variable domains are convenient formats for intrabodies, potentially allowing for intracellular functionality. Intrabodies are promising tools, capable of interfering with a wide range of molecular targets in various intracellular compartments. However, many significant challenges remain to be overcome before intrabodies can be useful therapeutic agents. Although major progress has been made in the design and selection of intrabodies, new developments and advances are needed to allow their efficient delivery and expression for treatment of human diseases.